What can probability forecasts tell us about inflation risks? - Juan Angel García; Andrés Manzanares (European Central Bank (ECB), 2007)
A crucial but often ignored element of inflation expectations is the amount of perceived inflation risk. This paper estimates the degree of uncertainty and asymmetry in the probability forecasts of the Survey of Professional Forecasters (SPF) using a new methodology. The main conclusion from our analysis is that, when monitoring inflation expectations, limiting attention to a point prediction is not sufficient. The analysis of inflation expectations should take into account inflation risks. As an example, we show that our measures of inflation risks can better explain why inflation scares happened in the bond market during the Volcker disinflation.
Keywords: C16; C42; E31; E47; 330; inflation expectations; inflation risk; power divergence estimators; skew-normal distribution; Survey of Professional Forecasters (SPF); Inflationserwartung; Inflation; Risiko; Glaubwürdigkeit; Zentralbank; Theorie; USA